Reflective Learning in Cross-Cultural and Cross-Disciplinary Virtual Classrooms - LUȘTREA, Anca; LUCHEȘ, Daniel; DINCĂ, Melinda (Presa Universitară Clujeană, 2023)
The Reflective learning in cross-cultural and cross-disciplinary virtual classrooms was elaborated under the auspices of the project “Bringing Real Life into Virtual Classrooms” (EEA 21-COP-0004), implemented by the West University of Timisoara, Romania, in partnership with the Norwegian University of Science and Technology, Norway, under the EEA Financial Mechanism 2014-2021. The book presents an analysis of the reflective practice of students who attended a joint course between UVT and NTNU, which involved experiential learning in transnational and cross-disciplinary groups of students. The students used digital and VR technologies to learn in a virtual environment.